The Influence of Work Commitment and Work Environment on Employee Performance in Bandarmasih Tempo Doeloe Area - Sari, Erini Junita; Hanifah, Hanifah; Ramadhan, Muhammad Reza Rizky (AIBPM Publisher, 2023)
ABSTRACT This study aims to examine the effect of work commitment and work environment on employee performance, using quantitative method. The samples were 39 employees in Bandarmasih Tempoe Doeloe area, taken using saturated sample technique. Data collection used questionnaire and analyzed using SPSS 25. The results of the study show that partially work commitment has effect on employee performance in Bandarmasih Tempoe Doeloe area, while environment does not. Simultaneously work commitment and work environment have influence on employee performance in Bandarmasih Tempoe Doeloe area. The t test significance level of Work Commitment is 95% (α = 0.05) with significance figure (P Value) of 0.025 < 0.05. This means that the work commitment variable has significant effect on employee performance variables (Y). The work environment variable’s significance (P Value) is 0.069 > 0.05, means that the work environment variable does not have significant effect on the Employee Performance variable (Y). The P value of the F test is 0.037, which means that the variables of Work Commitment (X1) and Work Environment (X2) have significant influence simultaneously on the Employee Performance variable (Y). Keywords: Work, commitment, environment